2022
DOI: 10.1017/cts.2022.370
|View full text |Cite
|
Sign up to set email alerts
|

What we wish every investigator knew: Top 4 recruitment and retention recommendations from the Recruitment Innovation Center

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Enhancing participation in clinical trials among historically underrepresented populations is a TIN challenge and commitment. Based on numerous TIN consultations, the RIC has developed recommendations to engage diverse communities in clinical trials, including proactively assessing recruitment and retention barriers, minimizing burden while returning value to participants, prioritizing data-driven site selection, and establishing multistage stakeholder engagement with minoritized communities …”
Section: Mrct Challenges and Tin Responsesmentioning
confidence: 99%
“…Enhancing participation in clinical trials among historically underrepresented populations is a TIN challenge and commitment. Based on numerous TIN consultations, the RIC has developed recommendations to engage diverse communities in clinical trials, including proactively assessing recruitment and retention barriers, minimizing burden while returning value to participants, prioritizing data-driven site selection, and establishing multistage stakeholder engagement with minoritized communities …”
Section: Mrct Challenges and Tin Responsesmentioning
confidence: 99%
“…The Recruitment Innovation Center (RIC) [ 9 , 10 ] Recruitment Materials resource line was developed to ensure study teams have resources to develop customized, authentic, engaging, culturally appropriate materials to maximize their impact. Broadly, the RIC works with Clinical and Translational Science Award (CTSA) hubs and their researchers to develop, test, and disseminate a range of innovations and resources to support studies’ recruitment and retention needs [ 11 ]. The Recruitment Materials resource line offers support for a variety of clinician- and participant-facing tools, including review and consultation on print materials, websites, and social media, as well as custom design, logos, templates, and development of mobile study applications.…”
Section: The Recruitment Innovation Centermentioning
confidence: 99%
“…While dissemination has been acknowledged to have highly variable definitions, we have used the term to refer to an intentional, active process of spreading information to target audiences (Baumann et al, 2022). Previous studies have shown that sharing summary research results (aggregate findings) with participants is an important practice that benefits both participants and researchers (Cook et al, 2022; Fernandez, Kodish, & Weijer, 2003; Hiratsuka et al, 2012; O'Daniel & Haga, 2011) with benefits including: building trust between communities and researchers, encouraging future research participation and understanding, and thanking participants for their contributions (Cook et al, 2022; Fernandez, Kodish, & Weijer, 2003; Hiratsuka et al, 2012; O'Daniel & Haga, 2011). Study participants largely desire to receive aggregate research findings and appreciate research teams who prioritize this practice (Aldinger et al, 2018; Dixon‐Woods et al, 2006; Hyams et al, 2016; Purvis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%